NATURAL RESOURCE MANAGEMENT PROBLEMS OF COASTAL AREAS AND SMALL ISLANDS IN THE ARU ISLAND - Tjiptabudy, Jantje; Rugebregt, Revency Vania; Alfons, S. S.; Laturette, Adonia I.; Saiya, Vica J. E. (Pattimura Law Journal, 2016)
On the territory of Aru in the management of natural resources. 3 Last year a lot of the problems occur. This is because their licensesÂ  natural resources management provided by the government to investors who want control over land in thisÂ  region, and explore them without regard to the ecosystem and the environment and indigenous people who live in it and in the end lead to conflict.